Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)13-2(x+1)=7
2.(x+1)=13-7
2.(x+1)=6
x+1=6/2
x+1=3
x=3-1
x=2
a, 13 - 2 ( x + 1 ) = 7
2 .( x + 1 ) = 13 - 7
2 .( x + 1 ) = 6
x + 1 = 6 : 2
x + 1 = 3
x = 3 - 1
x = 4
a)
5.(12-x)-20=30
⇒60-5x-20=30
⇒-5x=30+20-60
⇒-5x=-10
⇒x=2
b)(17x - 25 ) : 8 + 65 = 92
(17x - 25 ) : 8 + 65 = 81
17x - 25 = 16 x 8 = 128
17x = 128+25=153
x= 153:17 =9
c)
x=23
Giải thích các bước giải:
3x – 10 = 2x + 13
3x-2x=13+10
x=23
d)4(2x+7)-3(3x-2)=24
4.2x+4.7-3.3x+3.2=24
8x+28-9x+6=24
8x-9x=24-28-6=-10
=>(-1)x=-10
x=-10:(-1)
x=10
a. \(5\cdot\left(12-x\right)-20=30\Leftrightarrow5\left(12-x\right)=50\)
\(\Leftrightarrow12-x=50:5=10\)
\(\Leftrightarrow x=12-10=2\)
b. \(\left(17x-25\right):8+65=9^2\)
\(\Leftrightarrow\left(17x-25\right):8=81-65=16\)
\(\Leftrightarrow17x-25=16:8=2\)
\(\Leftrightarrow17x=2+25=27\Leftrightarrow x=\frac{27}{17}\)
c. \(3x-10=2x+13\)
\(\Leftrightarrow3x-2x=10+13\)
\(\Leftrightarrow x=23\)
d. \(4\cdot\left(2x+7\right)-3\cdot\left(3x-2\right)=24\)
\(\Leftrightarrow8x+28-9x+6=24\)
\(\Leftrightarrow34-x=24\Leftrightarrow x=10\)
\(3^2x-4-x^0=8\)
9x-4-1=8
9x-5=8
9x=13
=>x=\(\frac{13}{9}\)
(5^2.x+175):5+30=420+260
<=>(5^2.x+175):5=650
<=>5^2.x+175=3250
<=>25.x=3075
<=>x=123
( 52 . x + 175 ) : 5 + 30 = 420 + 65 . 4
= ( 25 . x + 175 ) : 5 + 30 = 420 + 260
( 25 . x + 175 ) : 5 + 30 = 680
( 25 . x + 175 ) : 5 = 680 - 30
( 25 . x + 175 ) : 5 = 650
25 . x + 175 = 650 . 5
25 . x + 175 = 3250
25 . x = 3250 - 175
25 . x = 3075
x = 3075 : 25
x = 123
a) 125 : x + ( 32 + 15 ) = 72
125 : x + 47 = 72
125 : x = 72 - 47
125 : x = 25
x = 125 : 25
x = 5
b) ( 35 + 135 ) - 2 . x = 86
170 - 2 . x = 86
2 . x = 170 - 86
2 . x = 84
x = 84 : 2
x = 42
c) 7 . x - 5 = 65
7 . x = 65 + 5
7 . x = 70
x = 70 : 7
x = 10
A) 125 / x + (32 + 15) = 72
125 / x + 47 = 72
125 / x = 72 - 47
125 / x = 25
x = 125 / 25
x = 5
a)\(2.x-138=8.9\)
\(2.x-138=72\)
\(2.x=72+138\)
\(2.x=210\)
\(x=210\div2\)
\(x=105\)
b)\(\left\{\left(6x-72\right)\div2-84\right\}.28=5628\)
\(\left(6x-72\right)\div2-84=201\)
\(\left(6x-72\right)\div2=285\)
\(6x-72=570\)
\(6x=642\)
\(x=107\)
c)\(420+65.4=\left(x+175\right)\div5+30\)
\(420+260=\left(x+175\right)\div5+30\)
\(680=\left(x+175\right)\div5+30\)
\(650=\left(x+175\right)\div5\)
\(3250=x+175\)
\(3075=x\)
65 - 4(2x-30)=5
-4(2x-30)=5-65
-4(2x-30)=-60
2x-30=15
2x=15+30
2x=45
x=45/2
65 - 4(2x - 30) = 5
=> 4(2x - 30) = 65 - 5
=> 8x - 120 = 60
=> 8x = 60 + 120
=> 8x = 180
=> x = 9/4